2013
DOI: 10.1093/ntr/ntt064
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Perceptions Toward Quitting Waterpipe Smoking Among Cafe Waterpipe Tobacco Smokers in Bahrain

Abstract: Waterpipe smokers in Bahrain cafés are frequent and high users. Health professionals must consider waterpipe smoking in all consultations and health promotion messages. A partnership between health professionals and disapproving members of families may be an effective strategy in encouraging waterpipe smokers to quit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
5
21
1
Order By: Relevance
“…The result of our study is consistent with the result of survey was conducted among Arab Americans in Houston, Texas, USA [27]. In contrast, two previous studies were performed on waterpipe smokers indicated that no significant association between age and intention of quitting waterpipe smoking [28,29]. Overall, 57.4% of the waterpipe users were not intended to quit waterpipe smoking.…”
Section: Socialize With Friends 3%supporting
confidence: 90%
“…The result of our study is consistent with the result of survey was conducted among Arab Americans in Houston, Texas, USA [27]. In contrast, two previous studies were performed on waterpipe smokers indicated that no significant association between age and intention of quitting waterpipe smoking [28,29]. Overall, 57.4% of the waterpipe users were not intended to quit waterpipe smoking.…”
Section: Socialize With Friends 3%supporting
confidence: 90%
“…Desire for quitting was related to physician’s advice, family’s attitude to shisha smoking, not considering own self being addicted and being a non-Bahraini [12]. This finding supports the important role of physicians in smoking cessation in Bahrain.…”
Section: Discussionmentioning
confidence: 63%
“…Studies on shisha intervention are scarce; however a recent review reported that interventions might help waterpipe smokers successfully quit smoking [11]. A study on waterpipe smokers in coffee shops in Bahrain reported that 82.0% expressed their ability to quit anytime, but only 40.0% wished to do so [12]. …”
Section: Discussionmentioning
confidence: 99%
“…However, individuals who are less dependent, have smoked for shorter periods of times, and who cite social stigma (e.g. family disapproval) as a reason to stop smoking make up the majority of waterpipe smokers interested in quitting (Borgan 2013; Ward 2005). These individuals may be less likely to benefit from pharmacological treatments.…”
Section: Discussionmentioning
confidence: 99%